2017
DOI: 10.1080/16549716.2017.1305765
|View full text |Cite
|
Sign up to set email alerts
|

Health-care utilization and associated factors in Gauteng province, South Africa

Abstract: Background: More than a billion people, mainly in low- and middle-income countries, are unable to access needed health-care services for a variety of reasons. Possible factors influencing health-care utilization include socio-demographic and economic factors such as age, sex, education, employment and income. However, different studies have showed mixed results. Moreover, there are limited studies on health-care utilization.Objective: This study aimed to determine health-care utilization and associated factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 24 publications
11
72
6
2
Order By: Relevance
“…Our findings further display the gender differential among newly-diagnosed PLHIV and ART initiation seen in similar studies [15, 20, 32]. Apart from differences explained by the underlying higher HIV prevalence in women versus men [4], gender differences in health seeking behavior for HIV care are likely influenced by targeted PMTCT programs for pregnant women.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings further display the gender differential among newly-diagnosed PLHIV and ART initiation seen in similar studies [15, 20, 32]. Apart from differences explained by the underlying higher HIV prevalence in women versus men [4], gender differences in health seeking behavior for HIV care are likely influenced by targeted PMTCT programs for pregnant women.…”
Section: Discussionsupporting
confidence: 79%
“…Finally, characteristics of the patients themselves are often highly predictive of timely initiation. Across Sub-Saharan Africa, women are more likely to initiate care in a timely manner than men, adolescents and young adults have been shown to seek timely care more than older adults, and individuals with higher income levels are more likely to seek care with timeliness than those with lower income levels [1315, 1720]. Studies similar to ours regarding timing of ART initiation in Sub-Saharan African (SSA) countries identified factors such as gender, age, location of residence, location of care facility, CD4 count, WHO stage, and TB co-infection as associated with timing of ART initiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the public health system was providing poor quality of care and yielding poor health outcomes due mainly to weak leadership and fragmentation of services at the implementation level. Leadership deficits and fragmentation of public healthcare services has also been observed in other South African studies [46][47][48] and research in Gauteng [49] showed that approximately 75% of randomly-selected participants indicated that they were no longer utilising public healthcare services due to the perceived diminished quality of these services. Thereupon, the 2014 Statistics South Africa general household survey indicated though that most (69%) households have a preference for public clinics and hospitals facilities first followed by a private doctor (29%) whenever a member falls ill [50], p. 28.…”
Section: Service Deliverysupporting
confidence: 58%
“…While children with female caregivers are further covered by HTS under the current index testing algorithm, children under the direct care of these fathers will be missed. The problem is compounded by a lower predilection for health-seeking, including HIV testing, among men than among women [45,46]. This highlights a need for a critical analysis of whether caregiver sex is associated with HIV infection in children, especially OVC.…”
Section: Gaps In Testing Coverage and Efficacy For Orphans And Vulnermentioning
confidence: 99%